Informacijos ieškojimas kontekste. Tamperės konferencijos pranešimų apžvalga - Macevičiūtė, Elena (Information & Media, 1997)
The International Conference on the study of information needs, seeking, and usage took place in Tampere on August 14-16, 1996. Over 30 authors presented the results of their research. The Conference showed that the previous orientation to the information system had changed. At present, information is perceived as a social phenomenon and information behaviour, as a process embedded in a wider context that cannot be ignored by researchers.